Pisati da bi se shvatilo: Sarajevo i Chicago na engleskom, bosanskom i poljskom - Ljevo-Ovčina, Amela (Przekłady Literatur Słowiańskich, 2017)
Writing to Understand: Sarajevo and Chicago in English, Bosnian and Polish The paper discusses Aleksandar Hemon's literary oeuvre through the prism of reception of The Book of My Lives in Bosnia-Herzegovina and Poland. In the present paper, we analyse the function of paratextual elements on the basis of the translations of the Bosnian-American author from English into Bosnian and Polish taking into consideration the fact that the author wrote in English, but reflecting on his Bosnian childhood, his youth, and the period after he moved to the United States of America. The present paper recognizes and emphasizes that Hemon, who writes in English without forgetting his mother tongue, is using subtle emphasis to describe the world and his place in it by means of calm but self-confident expression. The paratextual elements are used to direct and decompress, which enhances the experience of living and writing at two different places and in two languages so that once the experience has been transferred, its language is comprehensible, inspirational, and familiar to the reader. The paper analyses the title, biographical notes and other paratextual elements the editors and publishers selected to present the cultural aspects, the relevance, the quality of artistic persuasion and accomplishment, and the overall literary value as the truly essential value of this and all other literary works the role of which is to illuminate relations through experiences and contribute to understanding but also changing the human and the world. Keywords: English language, Bosnian language, Polish language, paratextual elements, publishers, reception, Aleksandar Hemon